2022
DOI: 10.1097/olq.0000000000001731
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Willingness to Use Daily Antibiotics as Sexually Transmitted Infection Prophylaxis Among HIV Preexposure Prophylaxis–Experienced Gay and Bisexual Men in Australia

Abstract: Background: Gay and bisexual men (GBM) who use HIV preexposure prophylaxis (HIV-PrEP) have high rates of bacterial sexually transmitted infections (STIs). The use of daily antibiotics as STI preexposure prophylaxis (STI-PrEP) may be appealing to GBM who are using or have previously used HIV-PrEP (HIV-PrEP-experienced) for the prevention of bacterial STIs. Methods:We examined willingness to use daily STI-PrEP among a cross-sectional sample of HIV-PrEP-experienced GBM in Australia who participated in an observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The effectiveness of public health strategies among MSM, such as bacterial STI prevention using doxycycline prophylaxis, depends on community and healthcare provider acceptance for success. Several studies, primarily based on surveys or interviews, indicate that the use of doxycycline for preventing bacterial STIs is generally accepted among MSM [33][34][35][36] .…”
Section: Community Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of public health strategies among MSM, such as bacterial STI prevention using doxycycline prophylaxis, depends on community and healthcare provider acceptance for success. Several studies, primarily based on surveys or interviews, indicate that the use of doxycycline for preventing bacterial STIs is generally accepted among MSM [33][34][35][36] .…”
Section: Community Acceptabilitymentioning
confidence: 99%
“…This percentage notably increased to 75.8% (95% CI: 74.0-77.6%) if chemoprophylaxis was shown to help reduce infections within this community 29 . Also in Australia, another online survey on 1347 MSM identified 54.3% willing to use DoxyPrep and linked willingness to participants with high number of sexual partners (> 10), recent methamphetamine use, being conscious about avoiding STIs, having a history of more STIs since starting HIV PrEP, and using condoms only on a partner's request 33 . In China, an online survey on 725 participants verified that willingness to use syphilis chemoprophylaxis was greater among those without a history of prior doxycycline use (p = 0.009).…”
Section: Community Acceptabilitymentioning
confidence: 99%
“…In the March issue, Arapali et al (https://journals.lww.com/stdjournal/Fulltext/2023/03000/Factors_Associated_With_Willingness_to_Use_Daily.4.aspx) describe the willingness of HIV PrEP-experienced MSM to use STI PrEP in Australia 4 . The study found that just over half (54%) of an online cohort of MSM reported willingness to use daily STI PrEP.…”
mentioning
confidence: 99%